Pengaruh Jumlah Produksi, Harga Ekspor, Dan Kurs Dollar Amerika Serikat Terhadap Volume Ekspor Batu Bara Indonesia Tahun 1992-2012 - Kumbayana, I Gusti Bagus; Swara, Wayan Yogi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
ABSTRACT Indonesia is a country that is very rich in natural resources revenue. The abundant wealth of course will be able to generate enormous profits. Coal exports may be affected by the amount of production, the export price and the US dollar exchange rate. The purpose of this study was to examine the effect of the amount of production, the price of exports and the United States dollar exchange rate against the volume of coal exports of Indonesia in 1992-2012. This study uses secondary data sourced from the Central Bureau of Statistics and Bank Indonesia are further analyzed using multiple linear regression analysis. The results based on multiple linear regression analysis showed that the effect of the amount of production, the price of exports and the United States dollar exchange rate simultaneously significant effect on the volume of coal exports of Indonesia in 1992-2012. However, partial, variable production quantities are positive and significant effect. Keywords: production number, export prices, the US dollar exchange rate, exports of coal